Fördomar Ennakkoluuloja Riksutställningar. (Stockholm : Liljevalchs Konsthall, 1993)
Ahtila, Eija-Liisa ; Antomsson, Lotta ; Antilla, Lauri ; Billgren, Ernst ; Grünstein, Raoul ; Hiltunen, Heli ; Johansson, Peter ; Lehtonen, Henrietta ; Lindberg, Maria ; Nilsson, Lars ; Niva, Jussi ; Rabina, Paavoo ; Sjolund, Stig ; Wolgers, Dan
Fördomar / Ennakkoluuloja, Liljevalchs Konsthall, Stockholm, 19 november 1993 - 09.01.1994, Traveling exhibition.
kunstcatalogus
Keywords: Zweden